2003
DOI: 10.1074/jbc.m213018200
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Molecular Characterization of Two Phosphatidic Acid-selective Phospholipase A1s, mPA-PLA1α and mPA-PLA1β

Abstract: We have identified a novel phospholipase A 1 , named mPA-PLA 1 ␤, which is specifically expressed in human testis and characterized it biochemically together with previously identified mPA-PLA 1 ␣. The sequence of mPA-PLA 1 ␤ encodes a 460-amino acid protein containing a lipase domain with significant homology to the previously identified phosphatidic acid (PA)-selective PLA 1 , mPA-PLA 1 ␣. mPA-PLA 1 ␤ contains a short lid and deleted ␤9 loop, which are characteristics of PLA 1 molecules in the lipase family,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
86
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 102 publications
(89 citation statements)
references
References 58 publications
3
86
0
Order By: Relevance
“…In this respect, our results showed that under PLA assay conditions LPA is formed from PA and that it could be rapidly converted into MAG and glycerol-3-phosphate by PLA or LPP and by LPA-phospholipase, respectively. This also agrees with other observations [18] according to which most of the PA generated by treatment with PLD in cells expressing PA-PLA forms is converted into LPA. Some of the PLA activities which hydrolyze either PC or PE have been identified in nuclei but they do not hydrolyze PA [36,38].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this respect, our results showed that under PLA assay conditions LPA is formed from PA and that it could be rapidly converted into MAG and glycerol-3-phosphate by PLA or LPP and by LPA-phospholipase, respectively. This also agrees with other observations [18] according to which most of the PA generated by treatment with PLD in cells expressing PA-PLA forms is converted into LPA. Some of the PLA activities which hydrolyze either PC or PE have been identified in nuclei but they do not hydrolyze PA [36,38].…”
Section: Discussionsupporting
confidence: 93%
“…PA-PLA activity was determined as described previously [18]. Lipids were extracted with chloroform:methanol (2:1, v/v) and washed with 0.2 volume of CaCl 2 (0.05%) [19].…”
Section: Pa-pla Assaymentioning
confidence: 99%
“…The content of choline phospholipids in the interstitial fraction of lung tissues was analyzed by mass spectrometry. MS analysis was performed according to previous reports (23,24) by using a Quattro Micro tandem quadrupole mass spectrometer (Waters) equipped with an ESI source. Phospholipid molecular species were separated and analyzed using normal-phase Cap-liquid chromatography ESI-MS with a silica column (Deverosil Si60, 150 ϫ 0.3 mm inner diameter, 5 m particle size, Nomura Chemicals, Nagoya, Japan).…”
Section: Construction Of the Targeting Vector And Generation Of Abca3mentioning
confidence: 99%
“…Mass spectrometric analyses were performed with a triple quadrupole instrument model Quattro micro (Waters, Milford, MA) equipped with an electrospray source as described. 22 The samples were provided by the UltiMate high-performance liquid chromatography system (Dionex Corp., Sunnyvale, CA) into the electrospray interface at a flow rate of 4 l/minute in a solvent system of acetonitrile-methanol-water (2:3:1) containing 0.1% ammonium formate (pH 6.4). The mass spectrometer was operated in the positive and negative scan modes.…”
Section: Cellular Phospholipid and Cholesterol Efflux Assaymentioning
confidence: 99%